Scuderoni v. Italy: Domestic Violence as a Systematic Failure of Italy (TEST Trento Student Law Review, 2025)
This article reflects on the phenomenon of domestic violence starting from the analysis of the recent judgement of the European Court of Human Rights (ECtHR) Scuderoni v. Italy, where the victim experienced a violation of the prohibition of ill–treatment and the right to respect for private life and correspondence, as established in Articles 3 and 8 of the European Convention on Human Rights, due to the inactivity of the Italian court which underestimated this problem. The analysis is then followed by a focus on the principal international conventions created to tackle gender – based violence and domestic violence, the Istanbul Convention and the European Convention on Human Rights, whose Articles 3 and 8 were violated by Italy. Ultimately, the phenomenon of domestic violence is analyzed from the Italian point of view, reporting data and measures that have been adopted to stop this form of violence. This is followed by a discussion on the delay of Italian authorities in recognizing domestic violence, the inadequacy of risk assessment to adopt preventive measures and to tackle the problem, with a consideration on the effectiveness of the investigations around the phenomenon of domestic violence.
Keywords: Domestic Violence; Human Rights; Delay of Institutions; Risk Assessment; Investigations